The Surface Layer Morphology of Si<Cr> Samples - Isaev, M.Sh.; Khudayberdieva, A.I.; Mamatkulov, M.N.; Asatov, U.T.; Kodirov, S.R. (East European Journal of Physics, 2024)
In this work, the electrical and photoelectric properties of the near-surface and surface layers of silicon doped by diffusion with chromium atoms were investigated. The formation of an anomalous concentration of charge carriers in these regions, as well as an anomalously low mobility, was revealed. The specific conductivity of the near-surface layer with a thickness of 1÷5 µm turned out to be equal to (1.6÷9.9)·103 Ohm-1·cm-1. The inhomogeneity of the crystal under study was determined by the light probe method.